Implementasi Integrasi Ilmu Pada Mata Pelajaran PAI di Sekolah Islam Nabila Kota Batam - Abdul Basir; Munzir Hitami; Abu Anwar (At-Tarbawi: Jurnal Kajian Kependidikan Islam, 2021)
The focus of study was Islamic schools which tries to adopt integration between religious knowledge and other sciences in their education system. Tthis study aims to find out how the integration of knowledge is implemented in the Nabila Islamic school in Batam, which in this case was selected as a sample in order to provide introductory data to examine the population of Islamic schools in Batam as a whole. The problems in this study were examined using a qualitative approach. From the data analysis, several findings can be identified as follows. Integration is implemented with a transdisciplinary method. The variants of the integration model at the Nabilah Islamic school are two of the eight other model variants, namely appreciation of various disciplines and coexistence.